Examining the Effectiveness of Infra-Low Frequency Neurofeedback on Cognitive and Clinical Components and Brain Signals in Patients with Parkinson’s Disease - Fadakaran, Zahra; Khosrowabadi , Reza; Saadat, Payam (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: The aim of the present study was to examine the effectiveness of infra-low frequency neurofeedback on cognitive and clinical components and brain signals in patients with Parkinson’s disease. Methods and Materials: The study population consisted of patients with Parkinson’s disease aged 50 to 95 years, with disease severity at stages 2 or 3 according to the Hoehn and Yahr criteria, who were referred to the neurology clinic of Ayatollah Rouhani Hospital in Babol. The final sample included 5 participants. During four phases of the study, participants completed computerized tests from the RehaCom software, the Unified Parkinson’s Disease Rating Scale, and the Montreal Cognitive Assessment. After the second pretest phase, each patient received 20 sessions of 30-minute infra-low frequency neurofeedback intervention based on the Othmer protocol (2017). Brainwave activity was recorded at each phase of the study. Behavioral data were analyzed using the paired-samples t-test, while brain signal data were analyzed using analysis of variance (ANOVA) and post hoc tests. Findings: The findings indicated improvements in motor and cognitive performance of participants at the follow-up stage compared to the pretest. Results from the RehaCom computerized tests demonstrated improvements in selective attention, working memory capacity, and logical reasoning. Additionally, the absolute power of gamma and beta brainwaves decreased, suggesting enhanced cognitive and emotional regulation in participants. Conclusion: The findings of this study indicate that infra-low frequency neurofeedback is effective in improving motor and cognitive functioning in individuals with Parkinson’s disease. Considering the results of the present study and the importance of non-invasive treatments in age-related disorders—particularly Alzheimer’s and Parkinson’s diseases—in enhancing cognitive and motor performance and slowing the progressive course of these disorders, greater attention to novel therapeutic approaches and further research is essential to address existing limitations and gaps in this field.